The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1095/biolreprod37.4.804
|View full text |Cite
|
Sign up to set email alerts
|

Luteal Function in the Bitch: Changes during Diestrus in Pituitary Concentration of and the Number of Luteal Receptors for Luteinizing Hormone and Prolactin1

Abstract: The concentration of unoccupied luteal receptors for luteinizing hormone (LH) and prolactin, and the concentration of these two hormones in the pituitary was determined in 11 groups of bitches (n = 3 or 4/group) representing stages from proestrus through Day 80 of diestrus. Despite dramatic changes in serum concentrations of progesterone, the concentration of luteal receptors for LH and prolactin was quite constant throughout the entire luteal phase. In association with the ovulatory surge of LH, pituitary con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1
4

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 30 publications
3
20
1
4
Order By: Relevance
“…This suggests that prolactin functions as the main luteotrophic factor in the cyclic dog during the second half of the luteal period. This conclusion is supported by the observation of Fernandes et al (7), that receptors for prolactin are more numerous than for LH in the dog.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This suggests that prolactin functions as the main luteotrophic factor in the cyclic dog during the second half of the luteal period. This conclusion is supported by the observation of Fernandes et al (7), that receptors for prolactin are more numerous than for LH in the dog.…”
Section: Discussionsupporting
confidence: 65%
“…Concentrations of receptors for LH and prolactin in the corpus luteum are quite constant throughout the entire luteal phase (7).…”
Section: Introductionmentioning
confidence: 98%
“…Serum concentrations of PRL remain mostly low during the first half of pregnancy, at approximately 5-6 weeks of gestation they begin to increase constantly towards parturition [14]. In non-pregnant animals serum concentrations of PRL remain low during most of the course of dioestrus and increase 2 to 3 fold around day 50 post ovulation, which is the time when parturition would have occurred [7,14,15]. Similarly, an increased availability of the luteinizing hormone (LH) has been observed in bitches when P4 concentrations were declining during the course of dioestrus [6,16].…”
Section: Introductionmentioning
confidence: 99%
“…As for the dog, and concerning the presence of PRLr in canine reproductive tissues, Fernandes et al [15] reported about the concentrations of the binding sites for prolactin in the luteal membranes isolated from tissue homogenates obtained from non-pregnant dogs during the course of dioestrus. They tended to be maximal during the first 40 days of the luteal life-span and were generally lower thereafter, when serum and luteal concentrations of P4 were decreasing [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation